Oral Test-Based Assessment in The Book Arabiyah Linnasyiin: An Alternative Assessment of Arabic Reading Skills - Al Usman, Semaun; Baroroh, R Umi; Thonthowi, Thonthowi; bin Aman, Adham (Universitas Ahmad Dahlan, 2023)
This study aims to Strategy the instrument for assessing the maharah qira'ah test in the book al-Arabiyah linasyi'in volume 5, and to analyze the instrument to be studied, qualitative research methods are used to examine comprehensively and in depth related to the quality of assessment, research This study uses descriptive qualitative, data used in this study in the form of fact findings or content of the material and patterns of the aspects of the questions in the assessment from the book al'arabiyah linasyi’in volume 5. It was found that there were four aspects of the assessment instrument that contained in the book include: understanding, pronunciation (ta'bir), mufradahat and use of language, and aspects of qawāid nahwu. This study focuses on aspects of maharah qirā'ah assessment. Based on the research results, there are updates in the assessment aspect using the method of reading aloud and silently with a rubric assessment system on a scale of 1-5 by determining quality, so that this scientific contribution can be used directly in the field of oral examinations.